THE IMPORTANCE OF LEARNING A SECOND LANGUAGE AND ITS BENEFITS FOR THE INDIVIDUAL - Tilavova, Malika (Журнал иностранных языков и лингвистики, 2021)
Learning language is a complex task that it requires you should have skills such as persistence, dedication, patience, and hard work. In addition, it has become a necessity and trend these days. In this article, we will break down the importance of learning a second language, some of the benefits of learning a second language and why this skill is one of the most overlooked skills in the world.